Perancangan Aplikasi Mobile Learning untuk Membantu Proses Pembelajaran di SDN Lemahireng 03 - Arfa Yustian (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2021)
Abstract Education is a milestone for a nation's civilization. Apart from that, the development of information technology is increasingly rapid in the current era of globalization and its impact on the world of education is inevitable. Along with the development of information technology, especially the internet in information systems, the teaching and learning process has made use of this information technology up to the basic education level. New innovations appear to support learning activities as a result of technological developments. One of these innovations is the use of a smartphone to become an interesting and fun learning medium when it is filled with an application and educational content. The use of smartphones has expanded to various groups, to students who have now used them. With this, it is hoped that research with the creation of an information system e-learning mobile application will help maximize the student learning process easily.